A Test of the Factor Endowments Model of Trade in a Rapidly Industrializing Country: The Case of Korea - Ramazani, Reza M.; Maskus, Keith E. (The Review of Economics and Statistics, 1993)
Reza M. Ramazani, Keith E. Maskus, A Test of the Factor Endowments Model of Trade in a Rapidly Industrializing Country: The Case of Korea, The Review of Economics and Statistics, Vol. 75, No. 3 (Aug., 1993), pp. 568-572